Fragmentation sociospatiale à Brasília et Curitiba : villes différentes, villes inégalitaires - Igor Catalão (Confins)
Difference and inequality are both apparently coincident notions. Even though, they do not have coincident implications in the production and appropriation of space. This is more obvious in the metropolises, which are more complex and heterogeneous spaces. This essay proposes to analyse how differences and inequalities, combined contradictorily, lead to the fragmented city. This analysis is based upon a comparison between the metropolitan agglomerations of Brasilia and Curitiba. The presented results are taken from a finished research made in both metropolises and they are used to discuss about the process of socio-spatial fragmentation. This process is explicated, on one side, by the permanence of the city-centre as a place that concentrates sophisticated urban goods and equipments and the periphery as an area of poverty and precariousness. On the other side, there is a requalification of the centre-periphery relation due to the increase of gated communities as preferred places to live in.